A novel thermoplastic shape memory polymer with solid-state plasticity derived from exchangeable hydrogen bonds. Issue 16 (4th March 2020) - Zhang, Xu; Sun, Guangping; Zhang, Xuequan
Abstract : Thermoplastic SMP equipped with a combination of performances including inherent reprocessability, satisfactory shape memory ability and swift shape re-configurability in the solid state. Abstract : A novel thermoplastic shape memory polymer (SMP) was synthesized by partly modifying the double bonds of trans -1, 4-polybutadiene (TPB) and subsequently introducing mono-isocyanate as pendant groups. The comb-like chains consisted of abundant hydrogen bonds on their side groups, which could readily assemble into dynamic non-covalent polymer networks. The physical crosslink net-points formed by the hydrogen bonds were utilized to anchor the permanent shape of PBTP, while the soft trans -1, 4-polybutadiene segments served as a switching phase to afford the temporary shape, and the glass transition temperature ( T g ) was taken as the switching temperature. The optimal result was obtained with the sample with 30% modification, which showed an excellent shape fixity ratio and inferior shape recovery ratio of 100% and 89.57%, respectively. According to the results of the stress relaxation test, the relaxation time for this sample is 27 s when heated at 70 °C, implying that the dynamic network inside the sample can undergo topological rearrangement rapidly while maintaining the network integrity during the process. The high density of exchangeable hydrogen bonds constitutes a highly crosslinked non-covalent network, the dynamic nature of which is responsible for this outstanding network topological structure rearrangement behaviour, and endows this SMP with solid-state plasticity to reconfigure its permanent shape in the absence of catalysts or moulds. The highly complex permanent shape reconfiguration at a moderate temperature within a rational period will greatly promote the practical use of SMPs, and enable a wide variety of future engineering applications.